2007
DOI: 10.1002/bem.20360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetic field on the antioxidant defense system of recirculation‐cultured Chlorella vulgaris

Abstract: Little is known about the influence of magnetic fields (MF) on growth of microalgae such as Chlorella vulgaris, which has been consumed as health food for various nutritional and pharmacological effects. This preliminary study investigated whether static MF can modulate the antioxidant system in C. vulgaris by exposing the cells to static MF generated by dual yoke electromagnets with magnetic flux density of 10-50 mT for 12 h. After exposure to 10-35 mT for 12 h, the activity of superoxide dismutases and perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 45 publications
6
48
2
Order By: Relevance
“…This hormetic response to EF was also observed during treatment of C. kessleri (Small, 2012) and C. vulgaris (Wang, 2008) cells with a static magnetic field. Gusbeth et al (Gusbeth, 2013) observed an increase of about 10-20% in biomass yield of C. vulgaris during 30 min treatment with low intensity pulsed electric field.…”
Section: Figuresupporting
confidence: 56%
See 2 more Smart Citations
“…This hormetic response to EF was also observed during treatment of C. kessleri (Small, 2012) and C. vulgaris (Wang, 2008) cells with a static magnetic field. Gusbeth et al (Gusbeth, 2013) observed an increase of about 10-20% in biomass yield of C. vulgaris during 30 min treatment with low intensity pulsed electric field.…”
Section: Figuresupporting
confidence: 56%
“…But at high treatment times, there are possibilities of irreversible electrical breakdown and free radical damage to the cells. The damage by the hydroxyl radicals can be neutralized by microalgae to an extent depending on the algal concentration (Wang, 2008). That is a possible explanation for a shift in the optimal treatment time from 30 min to 70 min with an increase in algal concentration from 0.25 g L -1 to 1.0 g L -1 .…”
Section: Algal Growth Retardation Through Enhanced Peroxide Accumulationmentioning
confidence: 98%
See 1 more Smart Citation
“…An orientation on free radicals' spin conditions by external MF and the energy increase as a result of this orientation accelerate chemical reactions in cell (Aladjanjiyan and Ylieva, 2003). Reactive half life of free radicals which occur during metabolic activity of organism increase by the effect of MF and antioxidant defense mechanism act as a protection from deleterious effects of these radicals (Sahebjamei et al, 2007;Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These increases were 80.39%, 73.45% and 62.32% for 19.8 s magnetic field applied experimental groups compared to the control, respectively. Various studies reported that MF increase enzyme activities of CAT, POX, and polyphenol oxidase (Lebedev et al, 1975;Pintilie et al, 2006;Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%